ASD Device Size to Patient Weight Ratio and Effect on Immediate Complications After Trans Catheter Closure in Pediatric Patients - Ikram, Madeeha; Mehmood, Amjad; Saeed, Maimoona; Ullah, Aziz; Murtaza, Hafiz Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine ASD device size to patient weight ratio and its effect on immediate complications after transcatheter ASD closure in pediatric patients.  Study Design: Analytical cross sectional studyPlace and Duration of Study: Department of Pediatric Cardiology, Armed Forces Institute of Cardiology/ National Institute of Health, Rawalpindi, from August 2025 to December 2025.Methodology: Thirty-eight pediatric patients (aged 1–12 years, 10–25 kg) with suitable ASD anatomy and symptomatic children were enrolled. Patients with > 25 kg, associated cardiac lesions requiring surgery, active infection, bleeding disorders, or contraindications to catheter intervention were excluded. Defect size was assessed by transthoracic echocardiography, and the ASD device size-to- patient weight ratio of patients was calculated. Patients were monitored for 24 hours postprocedure for immediate complications. Based on observed outcomes, patients were stratified according to device size-to- patient weight ratio for comparative analysis.Results: The ASD device size-to-patient weight ratio demonstrated a significant association with immediate complications. An optimal cut-off value of 1.53 was identified, dividing patients into a lower-risk group (≤1.53; 21(55.3%)) and a higher-risk group (>1.53; 17 (44.7%)). Overall, immediate complications occurred in 21.1% of patients. Complications were observed in 4.8% of patients in the lower-risk group compared with 41.2% in the higher-risk group, highlighting a substantially higher complication rate associated with increased device-to- .....Conclusion: An increased ASD device size-to- patient weight ratio is associated with a higher frequency of immediate complications following transcatheter ASD closure. Ratios exceeding 1.53 should be considered cautiously and reserved for cases where clinical benefits ...